THE ROLE OF SOCIAL STUDIES AND HISTORY LEARNING IN JUNIOR HIGH SCHOOL IN STRENGTHENING THE STUDENTS CHARACTER - Leo Agung S. (Paramita: Historical Studies Journal)
Nowadays, in Indonesia a variety of violence and moral degradation event still occur. The moral degradation phenomenon (among others) is indicated with the spread of violence, criminality, drug abuse, free sexual-intercourse and other misbehaviors. Multidimensional crisis and nation deterioration originates essentially in self-esteem, and failure in developing nations character education. Essentially, Social Science learning aimed to develop personal, social, and intellectual behavior. Thus, Social Science learning in Junior High Schools becomes a means and opportunity of strengthening the student characters such as sense of critical, discipline, environment awareness, social care, religious, having reading interest, loving to homeland, willing to sacrifice, creative, honest, independent, and hard work, in order to build the nation and the state better, more prosperous, secure, and peaceful.